Vitreous Hemorrhage in Pediatric Patients With X-Linked Retinoschisis Characteristics and Outcomes - da Cruz, Natasha F S (Ophthalmic surgery, lasers & imaging retina, 2023)
OBJECTIVE: To report the management and outcomes of vitreous hemorrhage in pediatric patients with X-linked retinoschisis (XLRS)